2016
DOI: 10.1021/acs.langmuir.5b03807
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Sensitive Supramolecular Switch Based on Mixed Carboxylic Acid Terminated Self-Assembled Monolayers on Au(111)

Abstract: We show that homogeneously mixed self-assembled monolayers (SAMs) of mercaptoalkanoic acids of different chain lengths can be used to build up a pH-sensitive supramolecular switch. The acids with short and long alkyl chains interact via the strong hydrogen bond between carboxylic acid groups. The pH acts as a trigger by breaking or restoring the hydrogen bond interaction in basic or acidic solutions, respectively. The corresponding changes in the monolayer structure were determined by ellipsometry, surface-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Interfacial acid–base chemistry of self-assembled monolayers (SAMs) has been employed in a wide range of applications, such as chemical sensing, biomedical devices, heterogeneous catalysis, and electronic devices, because it offers a feasible way to change the surface property by altering the environmental conditions. Since the past century, many techniques have been applied to investigate the surface chemistry of the immobilized pH-sensitive molecules, such as capacitance titrations, contact angle measurements, voltammetric measurements, and vibrational spectroscopy. , These studies have shown that the acid–base chemistry of surface-bound molecules can differ significantly from that in bulk solution, which is ascribed to the interaction of the immobilized molecules with the surface and the impact of the surface potential on the population of charged species at the interface. With all of these techniques, however, it is difficult to discriminate the individual molecule behavior from the average response .…”
mentioning
confidence: 99%
“…Interfacial acid–base chemistry of self-assembled monolayers (SAMs) has been employed in a wide range of applications, such as chemical sensing, biomedical devices, heterogeneous catalysis, and electronic devices, because it offers a feasible way to change the surface property by altering the environmental conditions. Since the past century, many techniques have been applied to investigate the surface chemistry of the immobilized pH-sensitive molecules, such as capacitance titrations, contact angle measurements, voltammetric measurements, and vibrational spectroscopy. , These studies have shown that the acid–base chemistry of surface-bound molecules can differ significantly from that in bulk solution, which is ascribed to the interaction of the immobilized molecules with the surface and the impact of the surface potential on the population of charged species at the interface. With all of these techniques, however, it is difficult to discriminate the individual molecule behavior from the average response .…”
mentioning
confidence: 99%
“…An explanation for lower surface activity on the −DiCOO – surface could be interlayer interaction between the carboxyl end groups. Hydrogen bonding between neighboring carboxylates has been reported to decrease the surface charge density . Such hydrogen bonding is more likely when the molecules in the SAM are not closely packed or when the surface to which the thiols bind is irregular .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding between neighbouring carboxylates has been reported to decrease the surface charge density. 61 Such hydrogen bonding is more likely when the molecules in the SAM are not closely packed or when the surface to which the thiols bind, is irregular. 62 Repulsion between oxygen atoms in the same malonate end group increases the separation angle between the two carbons that link the carboxyls, from 109 to 112-113 º (Figure 3b).…”
mentioning
confidence: 99%
“…Two‐component mixed SAMs are especially promising due to their strong potential to tune the physical and chemical properties of surfaces by changing the tail group, length, and chemical structure of the thiol molecular backbone. Therefore, SAMs have been utilized for various practical applications including pH‐sensitive supramolecular switches, protein adsorption, organic field‐effect transistors, and molecular electronic devices . Mixed SAMs on gold can be readily prepared using three methods: coadsorption of two different thiols, adsorption of asymmetric disulfides, and sequential adsorption .…”
Section: Acknowledgmentsmentioning
confidence: 99%